PENGARUH KONDISI KEUANGAN, LEVERAGE DAN REPUTASI AUDITOR PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Sari, Cendy Septania; Nasir, Azwir; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This research aims to test and prove empirically the influence of financialconditions, leverage and auditor reputation on going concern audit opinion. Thepopulation of this research is real estate and property companies listed on theIDX for the 2019-2021 period with a total sample of 58 companies. The samplingtechnique uses purposive sampling. The data analysis method used in thisresearch is a quantitative analysis technique with a logistic regression hypothesistesting formula which is processed with the help of a software program. Theresults of hypothesis testing show that the financial condition and leveragevariables have a significant effect on going concern audit opinion, while theauditor's reputation is not proven to have an effect.Keywords: Financial Condition, Auditor Reputation, Leverage and GoingConcern Audit Opinion